Veterinary and technical optimization of the fetal sheep model of congenital diaphragmatic hernia: implications for translational pediatric surgery - McCorkell, T. Connor; Espinosa Seoane, Daniela; Zani-Ruttenstock, Elke; Doktor, Fabian; Figueira, Rebeca; Sinclair, Melissa; zur Linden, Alex; Horna, Marta; Recchi, Lucciana; Defarges, Alice; Antounians, Lina; Bütter, Andreana; et al. (Frontiers in Surgery, 2025)
Congenital diaphragmatic hernia (CDH) is a life-threatening developmental anomaly where abdominal organs herniate into the thoracic cavity, impairing fetal lung growth and subsequent postnatal lung function. Despite advances in treatment, the morbidity and mortality of CDH remain significant. Currently, the most well-established fetal intervention is fetoscopic endoluminal tracheal occlusion (FETO), which promotes lung expansion and development by temporarily blocking the egress of lung fluid. However, treatment outcomes remain variable, which underscores the need for robust animal models to investigate novel therapies. The fetal sheep model is particularly valuable due to physiological similarities to human infants in lung development and anatomy. However, its successful implementation requires substantial veterinary and surgical expertise. In this paper, we outline the surgical protocol, refinements, and perioperative challenges in establishing a fetal sheep model of CDH to test a novel therapy. A diaphragmatic defect was surgically created via fetal thoracotomy at 80 days of gestation using a maternal caudal ventral midline laparotomy. Fetal tracheal occlusion with treatment administration was performed via a maternal left flank laparotomy at 108 days, followed by euthanasia then delivery at 136 days. Initial surgeries experienced complications such as maternal incisional dehiscence and herniation. These were mitigated through changes in surgical approach, closure techniques, and enhanced postoperative care. Veterinary oversight was critical in optimizing maternal well-being, minimizing stress, and improving recovery outcomes. This refined model provides a reproducible, welfare-centred approach integrating essential veterinary contributions to support translational pediatric surgery research in CDH.